(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the sonic features of isolation in Jen Silverman’s The Moors (2017), a psychological drama/dark comedy that seamlessly combines the two. Though the play has received wide critical acclaim for its thematic content and character relationships, there has been limited academic exploration of the role that sound, silence, and soundscapes play in furthering the play’s examination of isolation. By studying these sonic elements, this study aims to fill this lack, offering this new contribution to Silverman’s oeuvre. Founded upon Michel Chion’s film sound theory (1994), and particularly his concepts of "added value" and "subjective sound," this paper discusses the use of sound in Silverman not as backdrop but as a narrative device adding to the spectator’s understanding of the emotional and psychological loneliness of the characters. The analysis points out the ways in which aspects such as vocal delivery, silence, echo, and ambient sound are employed as metaphors for the internal conflict and isolation of the characters. The sound design in The Moors creates a physical sense of disconnection that serves to reinforce the play’s themes of longing, confinement, and reaching for togetherness. This article concluded that sound in The Moors forms the locus of its affective potential and the exploration of isolation, indicating how the sonic events trace the spectator’s relation to the character’s existential crises. The chapter offers new insights into the aesthetic and thematic intricacy of the play, making a case that consideration of the concept of isolation within contemporary drama necessarily requires critical consideration of sound and aurality.